Estimation of gross-structure parameters of giant dipole resonance: 1. A method - Uvarov, V.L.; Zakharchenko, A.A. (Вопросы атомной науки и техники, 2021)
Available data on photonuclear cross-sections, both measured experimentally and obtained on the basis of theoretical models, are characterized sometimes by a considerable spread. In work, a simple method for the estimation of width (FWHM) and maximum (σₘₐₓ) of excitation function of a reaction with dominant giant dipole resonance, is given. An analytical model is developed for the description of isotope production in an X-ray beam. It is shown, that the established yield of the reaction in a thin target, overlapping completely the beam with known end-point photon energy makes it possible to estimate the σₘₐₓ and FWHM values. The possibilities of new approach are demonstrated by a numerical experiment on the reference reactions. Наявні дані з фотоядерних перетинів, як такі, що одержані експериментально, так і на основі теоретичних моделей, інколи характеризуються значним розкидом. Описано простий метод оцінки ширини (FWHM) і максимуму (σₘₐₓ) функції збудження реакції з домінуванням гігантського дипольного резонансу. Розроблена аналітична модель для опису генерації ізотопів в пучку гальмівного випромінення. Показано, що за відомим виходом реакції у тонкій мішені, яка повністю перекриває пучок з наданою граничною енергією фотонів, можна встановити область значень σₘₐₓ та FWHM. Можливості нового підходу продемонстровані на референтних реакціях з використанням методу чисельного експерименту. Имеющиеся данные по фотоядерным сечениям, как полученные экспериментально, так и на основе теоретических моделей, иногда характеризуются значительным разбросом. Описан простой метод оценки ширины (FWHM) и максимума (σₘₐₓ) функции возбуждения реакции с доминированием гигантского дипольного резонанса. Разработана аналитическая модель для описания генерации изотопов в пучке тормозного излучения. Показано, что по известному выходу реакции в тонкой мишени, полностью перекрывающей пучок с заданной граничной энергией фотонов, можно установить область значений σₘₐₓ и FWHM. Возможности нового подхода продемонстрированы на референтных реакциях с использованием метода численного эксперимента.